(untitled) (Journal of Food and Dietetics Research, 2021)
Objectives: The present study was carried out with the objective of examining the cooking and sensory attributes of cauliflower leaves (Brassica oleraceavar. botrytis) incorporated homemade noodles. Material and Methods: Noodles in ratio 60:40 (WF:PMF) served as control and the cauliflower leaves puree (CLP) was incorporated to the control noodles in five different proportion such as 10, 20, 30, 40, and 50. The various blends were processed and shadow dried to prepare noodles. Both dry and cooked noodles were subjected to sensory evaluation by trained panel members and the cooking characteristics were estimated. Results: The water absorption of the noodles increases with increase in the level of CLP, cooking loss reduced with the level of CLP incorporation and was statistically significant at P <0.05 level. Sensory attributes between control and CLP-enriched dry noodles, only flavor and taste was statistically significant at P < 0.05 level. Conclusion: Owing the nutritive value of pearl millet, wheat, and cauliflower leaves, the noodles can replace the commercial noodles in household with minimum cost and can be popularized among foodies especially children and teenagers.